Analisis Financial Distress pada Perusahaan Konstruksi selama PSBB-PPKM era COVID-19 di Indonesia - Lucky Satria Budiman (Penerbit Goodwood, 2023)
Purpose: The purpose of this study is to analyze the extent of financial distress experienced by construction companies during the implementation of the PSBB-PPKM policy in the COVID-19 era during 2020-2022. Methodology/approach: This research methodology uses descriptive statistical analysis and review studies in a quantitative approach. The data used is secondary data sourced from the financial statements of construction companies that have been listed on the Indonesia Stock Exchange, then processed and analyzed using the Microsoft Excel application. Result/findings: During the implementation of the PSBB-PPKM policy, there were 31 samples of construction companies detected as financial distress, 12 and 20 samples of companies detected as grey area and safe zone. Financial distress companies occur because they have poor profitability ratios and the largest solvency ratios among other groups, gray area companies occur because they have large solvency ratios and poor profitability ratios, and safe zone companies occur because they have high liquidity and profitability ratios, and the smallest solvency ratios among other group companies. Limitation: The limitations of this study are the lack of consistent research analysis directions in previous journals, and not all sample company financial statements provide specific explanations of the development of account items in their financial statements. Contribution: This research can contribute as one of the main references of stakeholders to make decisions that can avoid losses in the current financial situation of construction companies in Indonesia in the future.